A comprehensive review on Bi2Te3‐based thin films: Thermoelectrics and beyond. Issue 1 (31st January 2022) - Tang, Xinfeng; Li, Ziwei; Liu, Wei; Zhang, Qingjie; Uher, Ctirad
Abstract: Bi2 Te3 ‐based materials are not only the most important and widely used room temperature thermoelectric (TE) materials but are also canonical examples of topological insulators in which the topological surface states are protected by the time‐reversal symmetry. High‐performance thin films based on Bi2 Te3 have attracted worldwide attention during the past two decades due primarily to their outstanding TE performance as highly efficient TE coolers and as miniature and flexible TE power generators for a variety of electronic devices. Moreover, intriguing topological phenomena, such as the quantum anomalous Hall effect and topological superconductivity discovered in Bi2 Te3 ‐based thin films and heterostructures, have shaped research directions in the field of condensed matter physics. In Bi2 Te3 ‐based films and heterostructures, delicate control of the carrier transport, film composition, and microstructure are prerequisites for successful device operations as well as for experimental verification of exotic topological phenomena. This review summarizes the recent progress made in atomic defect engineering, carrier tuning, and band engineering down to a nanoscale regime and how it relates to the growth and fabrication of high‐quality Bi2 Te3 ‐based films. The review also briefly discusses the physical insight into the exciting field of topological phenomena that were so dramatically realized in Bi2 Te3 ‐ and Bi2 Se3 ‐based structures. It is expected that Bi2 Te3 ‐based thin films and heterostructures will play an ever more prominent role as flexible TE devices collecting and converting low‐level (body) heat into electricity for numerous electronic applications. It is also likely that such films will continue to be a remarkable platform for the realization of novel topological phenomena. Abstract : Bi2 Te3 ‐based materials are one type of the most popular thermoelectric materials and topological insulators, whereby their thin films are particularly suitable for important applications in the efficient active cooling and self‐powered power supply for miniaturized/flexible electronic devices as well as in the low power electronics and quantum computation. Tremendous efforts regarding the delicate control of the atomic point defects, chemical composition, preferential orientation, magnetic doping, and also spin‐orbit coupling have been exerted for the optimization of electronic band structure, topological surface states, electrical and thermal transport, and topological electronic transport of Bi2 Te3 ‐based thin films, and hence for the proof‐of‐principle demonstration and practical applications of Bi2 Te3 ‐based thin film devices. It is widely accepted that Bi2 Te3 ‐based thin films will be of great significance for thin‐film thermoelectric applications and for discovering novel topological phenomena and relevant applications in the near future.